Blurring the Line: Digital Anonymity, Deception, and the Crisis of Online Authenticity - Comes, Brynn (Advances in Social Sciences Research Journal, 2025)
The digital age has changed how people present themselves online and perceive representations of the truth. This paper examines how online anonymity, disinformation, and identity reconstruction can undermine authenticity in digital spaces. Today, with over five billion social media users worldwide, the boundary between genuine and manufactured realities has been blurred by the rise of deepfakes, filters, and AI-generated content. This paper explores how anonymity creates conditions where fake content can thrive, accountability is reduced, and digital deception is normalized. It also discusses the motivating factors and consequences of spreading disinformation online. The paper further examines how identity reconstruction through curated personas leads to cognitive dissonance, loneliness, and the potential disintegration of authentic selfhood. Ultimately, it argues that unchecked anonymity and disinformation can pose ethical, psychological, and societal risks that impact digital integrity and democratic stability. Promoting media literacy, enforcing digital accountability, and developing AI-based content verification systems are essential to safeguarding authenticity in an era where online deception is rapidly increasing.